Hyperlipidemia Increases Nalbuphine Brain Accumulation with Multiple Dosing without Affecting Its Analgesic Response-Its Respiratory Depression Potential Should Be Investigated in Future Studies - Marwa E. Elsherbiny; May Almukainzi; Eman Amer; Marwan Emara (MDPI AG, 2024)
Nalbuphine is associated with a significant risk of respiratory depression. Its central nervous system entry is hindered by P-glycoproteins, and lower P-glycoprotein activity is a risk factor for respiratory depression. We assessed the effect of hyperlipidemia on nalbuphine pharmacokinetics, brain and liver uptake, and analgesic response following single (2.5 mg/kg) and multiple (2.5 mg/kg/day for three days) doses in normolipidemic and hyperlipidemic rats. Trends of reduction and increase in nalbuphine Cmax and Vdss/F were observed, respectively, in hyperlipidemic rats. Negative correlations were observed between Cmax and serum lipoproteins. Serum-normalized brain and liver levels at 1 h post-dose were lower in hyperlipidemic rats, with brain and liver levels being negatively and positively correlated with TG and HDL, respectively. At steady state, marked nalbuphine accumulation was observed in hyperlipidemic rat brains (R = 1.6) compared with normolipidemic rats (R = 1.1). Nalbuphine analgesic response was not altered by hyperlipidemia at steady state. Caution should be exercised since greater brain accumulation in hyperlipidemic patients treated with nalbuphine could increase their risk of respiratory depression. Our study highlights an unexpected role of lipoproteins in drug absorption and tissue uptake. We also propose a model for reduced nalbuphine absorption based on interaction with intestinal HDL-3.